Male cytogenetic evaluation prior to assisted reproduction procedures performed in Mar del Plata, Argentina - Poli, María Noelia (2016)
Objective: This paper aimed to estimate the frequency ofoccurrence and the types of chromosomal abnormalitiesfound in 141 infertile men with abnormal semen parameters.Methods: the frequency and type of chromosomal abnormalitieswere determined with male mitotic karyotypeanalysis from peripheral blood through chromosome bandingtechniques before assisted reproduction procedures.Results: In this series of 141 infertile men, 19 (13%) hadchromosomal anomalies and 35 (25%) had polymorphicvariants. The main chromosome abnormalities were reciprocaltranslocations and marker chromosomes in mosaic.Conclusions: These results stress the relevance of cytogeneticstudies for infertile males as a diagnostic tool anda valuable input in genetic counseling.